2021
DOI: 10.3390/molecules26175255
|View full text |Cite
|
Sign up to set email alerts
|

Natural Ingredients Common in the Trás-os-Montes Region (Portugal) for Use in the Cosmetic Industry: A Review about Chemical Composition and Antigenotoxic Properties

Abstract: The natural cosmetics market has grown since consumers became aware of the concept of natural-based ingredients. A significant number of cosmetics have an ecological impact on the environment and carry noxious and chemically potent substances. Thus, the use of natural and organic cosmetics becomes increasingly important since it is clear that topical treatment with cosmeceuticals can help improve skin rejuvenation. A substantial investigation into the benefits that fruits and plants can bring to health is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 159 publications
2
10
0
Order By: Relevance
“…Such potential cannot be ignored, and further investigation into how to incorporate this ingredient in a cosmetic should occur. Only two studies have been developed since 2012, showing that Elderberry has no mutagenic effect and a high in vitro activity [58]. However, none of them focused on cosmetic ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Such potential cannot be ignored, and further investigation into how to incorporate this ingredient in a cosmetic should occur. Only two studies have been developed since 2012, showing that Elderberry has no mutagenic effect and a high in vitro activity [58]. However, none of them focused on cosmetic ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…The following grape extracts can be used in cosmetics: fruit water, fruit extract, fruit powder, leaf water, leaf oil, leaf extract, leaf wax, leaf/seed skin extract, flower extract, seed extract, seed powder, bud extract, root extract, juice, skin powder, skin extract, vine sap, vine extract, juice extract, and shoot extract [ 122 ].…”
Section: Pharmaceutical Usementioning
confidence: 99%
“…SPF and photostability are currently enhanced by the natural antioxidant content of sunscreens. Studies have demonstrated the advantages of applying and ingesting polyphenols from several plant species, including Vitis vinifera, to protect against UV radiation [ 122 ]. Table 6 outlines relevant cosmetic varieties containing GSO.…”
Section: Pharmaceutical Usementioning
confidence: 99%
“…The most common varieties are "Parada", "Casanova", "Verdeal" and "Pegarinhos" [3]. It is also a region with the most organic farmers, and the climatic, topographic, and pedological differences predispose this region to agricultural diversity [4].…”
Section: Almondsmentioning
confidence: 99%